2016
DOI: 10.1002/joc.4824
|View full text |Cite
|
Sign up to set email alerts
|

Extension of summer climatic conditions into spring in the Western Mediterranean area

Abstract: From a local point of view, in May/June, there is an important and positive 2 m temperature trend at Palma (Mallorca), which is simultaneous and highly correlated with a strong increase in the 500 hPa geopotential height. This study analyses this fact as well as the observed tendencies in a wider seasonal and geographical context. We confirm the particularly high correlation between 2 m temperature and 500 hPa geopotential during the warm months as opposed to the much weaker correlation in winter. This suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
(61 reference statements)
2
10
0
Order By: Relevance
“…Likewise, warming is not homogeneous throughout the year and in the Mediterranean region the greatest contribution to annual warming occurs in the transition from spring to summer (Garcia, 2015). There is also strong evidence to suggest that summer seasons in the Mediterranean are becoming longer (Bartolini et al ., 2012; Jansà et al ., 2017). In this sense, despite the short climatic period analysed in our study, warming trends (with respect to maximum temperatures) were observed in April, September and December, and also marginally in May.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, warming is not homogeneous throughout the year and in the Mediterranean region the greatest contribution to annual warming occurs in the transition from spring to summer (Garcia, 2015). There is also strong evidence to suggest that summer seasons in the Mediterranean are becoming longer (Bartolini et al ., 2012; Jansà et al ., 2017). In this sense, despite the short climatic period analysed in our study, warming trends (with respect to maximum temperatures) were observed in April, September and December, and also marginally in May.…”
Section: Discussionmentioning
confidence: 99%
“…Although all five sites were used to define the overall phenology of the species on the island, we only used three with 15–18 years of data for comparisons: (1) Albufera des Grau, an open coastal area with dry meadows and Mediterranean scrub; (2) Santa Catalina, a forested area dominated by evergreen oak and pine forests; and (3) Barranc d’Algendar, a ravine in the south of the island with orchards at the beginning and thick undergrowth further inland. Although the climate is typically Mediterranean throughout the island, with hot-dry summers and mild-wet winters (Jansà et al, 2017), the geomorphology of its ravines generates moister microclimatic conditions that set Barranc d’Algendar apart from the other studied localities.…”
Section: Methodsmentioning
confidence: 99%
“…Although all five sites were used to define the overall phenology of the species on the island, we only used three with 15–18 years of data for comparisons: (1) Albufera des Grau, an open coastal area with dry meadows and Mediterranean scrub; (2) Santa Catalina, a forested area dominated by evergreen oak and pine forests; and (3) Barranc d'Algendar, a ravine in the south of the island with orchards at the beginning and thick undergrowth further inland. Although the climate is typically Mediterranean throughout the island, with hot‐dry summers and mild‐wet winters (Jansà et al ., 2017), the geomorphology of its ravines generates moister microclimatic conditions in Barranc d'Algendar.…”
Section: Methodsmentioning
confidence: 99%
“…Within Europe, the Mediterranean is an area especially susceptible to some aspects of climate change [7], and has had significantly greater consequences from some of its effects. For instance, the warming effect is stronger in the Mediterranean region [8], as well as unevenly distributed within the months of the year [9]. The United Nations Environment Programme (UNEP) [10] states that there is a need for an investment in renewable energy sources and an increase in their efficiency in the Mediterranean region, due to the need for an equilibrium in the use of food, water and energy.…”
Section: Introductionmentioning
confidence: 99%